CA125 modified by PLT and NLR improves the predictive accuracy of adenomyosis-derived pelvic dense adhesion. Issue 19 (May 2017) - Jiang, Caixia; Liu, Chao; Guo, Jing; Chen, Li; Luo, Ning; Qu, Xiaoyan; Yang, Weihong; Ren, Qing; Cheng, Zhongping
Abstract : Abstract: To explore the value of serum levels of CA125, platelet count (PLT), neutrophil–lymphocyte ratio (NLR), and modified CA125 markers CA125a and CA125b in predicting pelvic dense adhesion (PDA) associated with adenomyosis, CA125a = lg(CA125 × PLT × 10 9 ), CA125b = lg(CA125 × NLR). This retrospective study included 304 patients who underwent surgery for adenomyosis. Correlations of serum levels of CA125, PLT, NLR, and modified CA125 markers with adenomyosis-derived PDA were analyzed by Logistic regression. Receiver operating characteristic curve was applied to assess the utility of these parameters for predicting PDA. All the parameters including CA125, PLT, NLR, and modified CA125 markers were positively correlated with PDA ( P  < .05 or P  < .01). More importantly, CA125a was more specific (85.03% vs. 83.00%) and more sensitive (47.56% vs. 47.47%) than CA125 alone for the prediction of PDA, and CA125b could also improve the predictive specificity of PDA (53.13% vs. 47.47%). Serum CA125, PLT, and NLR were all closely correlated with PDA in adenomyosis patients. CA125 modified by PLT and NLR could further improve the predictive accuracy of adenomyosis-derived PDA, thus providing more meaningful references for better-informed decisions about the mode of surgical access for the clinical treatment of adenomyosis.